A schematic diagram for the main task conditions. - Mohammed M. Alnawmasi (11156577) (2025)
The target stimulus was initially presented for 1 second, followed by the search stimulus, which was presented for 250 ms. The task of the participant was to indicate whether the target stimulus was present or absent.